Appealing to altruism: an alternative strategy to address the health workforce crisis in developing countries? - Smith, R; Lagarde, M; Blaauw, D; Goodman, C; English, M; Mullei, K; Pagaiya, N; Tangcharoensathien, V; Erasmus, E; Hanson, K (2013)
BACKGROUND: Recruitment and retention of health workers is a major concern. Policy initiatives emphasize financial incentives, despite mixed evidence of their effectiveness. Qualitative studies suggest that nurses especially may be more driven by altruistic motivations, but quantitative research has overlooked such values. This paper adds to the literature through characterizing the nature and determinants of nurses' altruism, based on a cross-country quantitative study. METHODS: An experimental 'dictator game' was undertaken with 1064 final year nursing students in Kenya, South Africa and Thailand between April 2007 and July 2008. This presents participants with a real financial endowment to split between themselves and another student, a patient or a poor person. Giving a greater share of this financial endowment to the other person is interpreted as reflecting greater altruism. RESULTS: Nursing students gave over 30% of their initial endowment to others (compared with 10% in similar experiments undertaken in other samples). Respondents in all three countries showed greater generosity to patients and the poor than to fellow students. CONCLUSIONS: Consideration needs to be given to how to appeal to altruistic values as an alternative strategy to encourage nurses to enter the profession and remain, such as designing recruitment strategies to increase recruitment of altruistic individuals who are more likely to remain in the profession.